BEHAVIORAL PATTERNS OF GENERATION Z WHEN HANGING OUT AT AFFAN COFFEE FROM A SOCIAL COMMUNICATION PERSPECTIVE - Fadly Raihan Nugroho; RR. Roosita Cindrakasih (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This study examines the hangout (nongkrong) behavioral patterns of Generation Z at Affan Coffee from a social communication perspective. Café hangout culture has evolved beyond mere consumption into a social space supporting interaction, idea exchange, and identity formation. Using a descriptive qualitative approach, data were collected through observation, semi-structured interviews, and documentation. Informants were selected via purposive sampling—three visitors aged 23–27 who qualify as Gen Z. Findings show: (1) Gen Z chooses Affan Coffee for its comfortable atmosphere, adequate facilities, strategic location, and affordable prices; (2) hangout activities are multifunctional, including casual conversation, group work, work-from-café, and gaming together; (3) hangout is perceived as a transitional space to reduce stress, maintain social connections, and express identity. Results are analysed through George Herbert Mead's Symbolic Interactionism—specifically the concepts of Mind, Self, and Society—revealing that hangout activity is a social process that constructs meaning, identity, and interpersonal relationships.